Alzheimer's disease in the United Kingdom: developing patient and carer support strategies to encourage care in the community. Issue 3 (September 1997) - Hunter, R; McGill, L; Bosanquet, N; Johnson, N
Abstract : Alzheimer's disease is a growing challenge for care providers and purchasers. With the shift away from the provision of long term institutional care in most developed countries, there is a growing tendency for patients with Alzheimer's disease to be cared for at home. In the United Kingdom, this change of direction contrasts with the policies of the 1980s and 90s which focused more attention on controlling costs than on assessment of the needs of the patient and carer and patient management. In recent years, the resources available for management of Alzheimer's disease have focused on institutional care, coupled with drug treatment to control difficult behaviour as the disease progresses. For these reasons, the current system has led to crisis management rather than preventive support–that is, long term care for a few rather than assistance in the home before the crises occur and institutional care is needed. Despite recent innovations in the care of patients with Alzheimer's disease, the nature of the support that patients and carers receive is poorly defined and sometimes inadequate. As a result of the shift towards care in the community, the informal carer occupies an increasingly central role in the care of these patients and the issue of how the best quality of care may be defined and delivered is an issue which is now ripe for review. The objective of this paper is to redefine the type of support that patients and carers should receive so that the disease can be managed more effectively in the community. The needs of patients with Alzheimer's disease and their carers are many and this should be taken into account in defining the quality and structure of healthcare support. This paper shows how new initiatives, combined with recently available symptomatic drug treatment, can allow patients with Alzheimer's disease to be maintained at home for longer. This will have the dual impact of raising the quality of care for patients and improving the quality of life for their carers. Moreover, maintaining patients in a home environment will tend to limit public and private expenditure on institutional care due to a possible delay in the need for it.